Financial Performance and Corporate Social Responsibility: An Empirical Study of Indonesian Islamic Commercial Banks (2020–2024) - Aris, Muhammad rizqie; Selamet (urn:multiple://2988-7828multiple.v3i64)
The goal of this study is to look at how financial success affects the disclosure of Corporate Social Responsibility (CSR) in Indonesian Islamic commercial banks between 2020 and 2024. Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin (NPM) are all used to measure a company's financial success. A disclosure index based on Global Reporting Initiative (GRI) criteria is used to measure Corporate Social Responsibility (CSR). The method of analysis used is multiple linear regression on panel data from ten general sharia banks that are registered with the OJK. The results of the study show that ROA and ROE have a positive and significant effect on CSR disclosure, but NPM does not have a significant effect. This study shows how important financial achievement is for Islamic banks' social participation.